Mobile Bank from an Islamic Economic Perspective - Gunaepi, Aang; Bianda, Ryan; Misbakul Munir , Muhammad (Journal of World Science, 2023)
Mobile banking is a widespread practice in many areas throughout Indonesia. There are many reasons for this, both internal and external. This study aims to find out and analyze the definition, history, and practice of mobile banking, then review it from the perspective of Islamic Economics. This study uses a qualitative method by reviewing related literature on mobile banking and its practices in various regions in Indonesia. In the Islamic economy, financial inclusion is very important because the financial system is geared to promote people's welfare. The practice of debts through mobile banks can be carried out with several principles that must be obeyed, including murabahah, mudharabah, and musyarakah. During obligations through portable banks, mobile banks must ensure that all transactions follow sharia principles. The Islamic solution to preventing the practice of mobile banking is to carry out financial planning through a priority scale of needs, educate the public about the Islamic economy through Islamic financial institutions, and maximize the role of zakat for mustahik.